SINTESIS 6-NITRO VERATRALDEHID (3,4-DIMETOKSI-6-NITRO BENZALDEHID) DARI VANILIN DENGAN HNO3 DAN CAMPURAN HNO3-H2SO4 - Undri Rastuti; Jumina Jumina; Sabirin Matsjeh (Molekul, 2009)
The synthesis of 6-nitro veratraldehyde from vanillin was used HNO3 and a mixture of HNO3 and H2SO4. The reaction steps were (I) methylation of vanillin and (2) nitration of the methylation product. Methylation of vanillin was conducted using dimetnylsulfate and NaOH at 60 0C for 2 hours. Nitration of the methylation product was performed in two methods, which using HN03 and using a mixture of HN03 and H2SO4 both at 5 0C for 2 hours. The products were analyzed by means of TLC, GC; IR, 1H-NMR and GC-MS spectrometers.The methylation of vanillin gave 87.7 % yield of veratraldehyde which was found as a white crystal (m.p 43 oC). The nitration of veratraldehyde produced 6-nitro veratraldehyde observed as a yellow crystal having of m.p. 1300C. Nitration using neat HNO3 gave a smaller yield (50.35%) of 6-nitro veratraldehyde than nitration with a mixture of HNO3 and H2SO4 (93.63 %).